Simple automatic hydroponic system / Muhammad Fathi Fikri Burhan, Muhammad Akmal Jamil and Muhammad Alif Asyraf Ghazali - Burhan, Muhammad Fathi Fikri; Jamil, Muhammad Akmal; Ghazali, Muhammad Alif Asyraf (2015)
This project is a system that helps farmer to make their work easy and more systematic. We know that farmer always had to change the water in the tank and give their plants fertilizer using spray by themselves. This project also reduces a human energy to work time by time based on growth the plant. This system manually fertilize from time to time, make the auto fertilizer by using spray system. Furthermore, auto water pump timer system is to make it auto refill and stop before over flooded. This system can be shut down by its own when time ended. In addition, water level indicator system is to level the water to avoid from overflow into the tank